THE USE OF VISUAL TECHNOLOGIES FOR THE DEVELOPMENT OF SPEECH IN PRESCHOOL CHILDREN (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article reveals the possibilities of developing coherent speech of preschool children using visual technologies, in particular, the criteria of manufacturability, methods of structuring information, principles of visualization technology of educational information are disclosed.